(untitled) (Homoeopathy for All, 2023)
Homoeopathy is a unique system of medicine based on individualization and symptom similarity of the patient. It treats sickness of a man as a whole and individualised entity. Homoeopathy can help in the treatment of various skin conditions, as it can be seen from the case report presented of a 21 years old girl who was suffering from furuncle since 2 weeks and treated within 1 week with Homoeopathic similimum which was selected on the basis of individualisation.